Pengalaman Masyarakat Aceh Selatan Terkait Perilaku Kesehatan Selama Pandemi COVID-19 - Kawati, Salma Merda; Suza, Dewi Elizadiani; Tarigan, Amira Permatasari (Journal of Telenursing (JOTING), 2024)
This study aims to explore in depth the experiences of the people of South Aceh related to health behavior during the COVID-19 pandemic. The research method uses a descriptive phenomenological approach with an in-depth interview process, making interview transcripts and then analyzing the data using the Collaizi analysis method. The study results showed four themes: community efforts to prevent COVID-19, psychological disorders, activities carried out during the COVID-19 pandemic, and difficulties in implementing COVID-19 prevention efforts. The conclusion is that most of the community's behavior is positive, and the community has implemented prevention efforts well, even though some religious and traditional events have been carried out during the COVID-19 pandemic. Keywords: COVID-19, Community, Experience, Health Behavior